Unveiling the Dominant Role of Satisfaction and Trust in Shaping Customer Loyalty: An Empirical Study of Four-Wheel Automotive Refinancing Services in Indonesia - Irma Hayani; Tanti Novianti; Netti Tinaprilla (Transpublika Publisher, 2025)
This research examines how customer satisfaction and trust impact customer loyalty within Indonesia's four-wheel automotive refinancing sector. Through a quantitative survey approach, information was gathered from 119 participants who had previously utilized refinancing services at PT X, an organization associated with a prominent automotive manufacturer. The study employed the SERVQUAL framework to measure service quality, complemented by Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) to gauge customer attitudes and satisfaction rates. Partial Least Square Structural Equation Modeling (PLS-SEM) was utilized to analyze the interconnections between satisfaction, trust, and loyalty variables. Results demonstrate that customer satisfaction significantly and positively influences both trust and loyalty, with trust also showing a substantial impact on loyalty. Empathy and responsiveness were identified as critical service dimensions needing enhancement. The overall CSI value of 79.8% indicates customers are